Transcriptome analysis unveils the functional effects of ectomycorrhizal fungal colonization on cadmium tolerance of willow saplings - Wang, Lijiao; Yang, Baoshan; Wang, Hui; Shi, Jiaxing; Dong, Jinhao; Zhao, Xiaoxia; Qin, Guanghua; He, Xinhua; Wang, Meiyuan (Frontiers in Microbiology, 2025)
IntroductionEctomycorrhizal fungus (ECMF) could enhance plant tolerance to heavy metal toxicity by altering metal accumulation and protecting plants from oxidative injury. However, the molecular mechanisms underlying ECMF-mediated detoxification of cadmium (Cd) in willow sapling are not well known. This study aimed to unveil the roles of Cenococcum geophilum (CG) and Suillus luteus (SL) in regulating Cd toxicity tolerance in willow (Salix psammophila ‘Huangpi1’) saplings.MethodsThis study systematically evaluated physiological and biochemical parameters in the leaf and root tissues of 18 willow saplings, while concurrently conducting transcriptomic analysis of the roots under Cd stress. The specific treatments were labeled as follows: NF (no ECMF inoculation and no Cd addition), CG (CG colonization only), SL (SL colonization only), NF+Cd (no ECMF inoculation with 100 μM Cd addition), CG+Cd (CG colonization with 100 μM Cd addition), and SL+Cd (SL colonization with 100 μM Cd addition).ResultsThe results showed the growth, photosynthesis, antioxidant system and transcriptome of 2-month-old willow saplings responded differently to ECMFs colonization under Cd stress. S. luteus markedly increased the aerial parts biomass, while C. geophilum significantly enhanced the root property indices of willow saplings under Cd stress. The highest number of differentially expressed genes (DEGs) was observed in the comparison between CG+Cd (CG colonization with 100 μM Cd addition) and NF+Cd (no ECMF inoculation with 100 μM Cd addition). C. geophilum colonization activated plant hormone signal transduction and carbohydrate metabolism pathways, while S. luteus enhanced the synthesis of secondary metabolites.DiscussionThis study provides a molecular perspective on the mechanism of interaction between ECMFs and willow saplings under Cd stress and supports the application of ECMFs for phytoremediation of Cd-contaminated soil.